Strategic Management Capabilities in Child Identity Card (Kartu Identitas Anak) Program in Civil Registry Service Office of Depok City - Cindy Ni Nyoman Sadvaraz; Zuliansyah Putra Zulkarnain (Jurnal Manajemen Pelayanan Publik, 2021)
This article aims to analyze the strategic management capabilities of Population and Civil Registry Service Agency/PCRSA (Dinas Kependudukan dan Catatan Sipil/Dukcapil) of Depok City in administering the Child Identity Card/CIC National Program. Considering the scope and the high level of complexity, the Ministry of Home Affairs/MoHA picked several local governments as pilot project, and one of them is the Depok Government. This selection is inseparable from the Depok City priority program, namely Child Friendly City which has been launched one year before the CIC Program was started by MoHA in 2017. However, the CIC program could not meet the target set. To analyze these problems, this article employs the strategic management capabilities dimension. By using PCRSA of Depok City as the case study, this article explains the presence of the following strategic management capabilities: (a) the ability to manage authority indicates that the hierarchical based authority practice is not based on development of ideas and knowledge; (b) integration of system and structure is not yet achieved thoroughly across organizations of Depok City Government, instead, it is limited to PCRSA; (c) networking between PCRSA and private sector tend to be passive and is not built upon common goals and exchange of resources between actora; and (d) changes in ideas and strategic plans are still sporadic mainly due to COVID-19 pandemic, even though the need for change has appeared before the pandemic, such as the application of electronic-based services.